2019
DOI: 10.1021/acsabm.9b00347
|View full text |Cite
|
Sign up to set email alerts
|

Light-Responsive Serinol-Based Polycarbonate and Polyester as Degradable Scaffolds

Abstract: Stimuli-responsive self-immolative aliphatic polycarbonates (APCs) and polyesters (APEs) have attractive advantages for biomedical and pharmaceutical applications. In the present work, polycondensation of o-nitrobenzyl-protected serinol was explored as a simple route to obtain light-responsive polycarbonate (LrPC) and polyester (LrPE). By exposure to UV light, these polymers decomposed rapidly and completely into oligomers and small molecules, as detected by size exclusion chromatography (SEC), UV/vis, and 1H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…By exploiting similar strategy, Kuckling and Sun have recently developed a new light‐responsive aliphatic polycarbonate (LrPC) for delivery of the photosensitizer 5,10,15,20‐tetrakis (m‐hydroxyphenyl)chlorin (mTHPC) ( Figure ). Multiple photocleavable oNB groups were conjugated within this LrPC polymer as side chains . UV light irradiation (λ = 320–480 nm) resulted in the cleavage of the oNB protecting groups, followed by the rapid degradation of the polymers via intramolecular cyclization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…By exploiting similar strategy, Kuckling and Sun have recently developed a new light‐responsive aliphatic polycarbonate (LrPC) for delivery of the photosensitizer 5,10,15,20‐tetrakis (m‐hydroxyphenyl)chlorin (mTHPC) ( Figure ). Multiple photocleavable oNB groups were conjugated within this LrPC polymer as side chains . UV light irradiation (λ = 320–480 nm) resulted in the cleavage of the oNB protecting groups, followed by the rapid degradation of the polymers via intramolecular cyclization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…This polymer was designed for application as a stimuli-responsive nanoparticulate drug delivery system for hydrophobic drugs. In a similar approach, an APC was formed that degraded upon photo-activated cleavage of a protecting group to yield a primary amine [113][114][115] (Figure 11H) to produce nanoparticles to be used in photodynamic therapy.…”
Section: Degradation By Intramolecular Cyclizationmentioning
confidence: 99%
“…Similarly, Fang et al [146] reported photo-responsive micelles consisting of PNIPAM-b-poly(3-methyl-3-nitrobenzyl-trimethylene carbonate) for indomethacin drug delivery system. Likewise, Kuckilng and coworkers developed a series of light-degradable nanocarriers consisting of PEGylated APC with an o-nitrobenzyl ester group as side chains [147][148][149][150][151]. The nanoparticles were prepared from mixing amphiphilic APC copolymer with poly(lactide-co-glycolide) in ratio 1:3 (Figure 9).…”
Section: Light-responsive Apc Nanocarriersmentioning
confidence: 99%
“…Preliminary in vitro cellular studies of the above-mentioned nanoparticles and degradation products confirmed that systems have the potential to be used for in vivo studies. [147][148][149][150][151]. The nanoparticles were prepared from mixing amphiphilic APC copolymer with poly(lactide-co-glycolide) in ratio 1:3 ( Figure 9).…”
Section: Light-responsive Apc Nanocarriersmentioning
confidence: 99%